2018
DOI: 10.4186/ej.2018.22.3.165
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Lithium Ion from Lithium-Cobalt Mixture using Electrodialysis Monovalent Membrane

Abstract: Electrodialysis is a separation process which ions are transported through semi permeable membranes under an influence of electric potential. In this research, electrodialysis using monovalent ion exchange membranes was applied to separate lithium ions from mixtures of lithium-cobalt aqueous solution. The study aims to examine factors that affect the performances of electrodialysis monovalent membrane, such as applied voltage, flow rate, and the concentration of cobalt as co-ion. The research was conducted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
(46 reference statements)
1
11
1
Order By: Relevance
“…Neosepta The high selectivity of the Neosepta ® monovalent-selective cationic exchange membrane results in higher faradic efficiency for lithium(I) and higher permselectivity indexes for lithium(I) with respect to the different divalent cations. The permselectivity index for the Neosepta ® monovalent-selective cationic exchange membrane (P Li/Co = 5.6) is slightly lower than those reported in the work of Afifah et al (2018) [17], i.e., P(Li/Co) = 6.75 at a flowrate of 15 L h −1 and for a voltage of 3 V/Cell with a pack containing 5 pairs of monovalent selective membranes PC-MVA/PC-MVK (initial lithium(I) and cobalt(II) concentration = 100 mg L −1 and 300 mg L −1 , respectively) against P(Li/Co) = 5.6 in this study. However, the value reported in our work regarding the permselectivity index for lithium(I) toward manganese(II) is greater than that obtained by Chan et al [13] (P(Li/Mn) = 5.4 in the present study against P(Li/Mn) = 2.81 at a flowrate of 45 L h −1 and for a voltage of 6 V/Cell with a pack containing 2 pairs of standard anionic membranes PCA PC 400D and 2 Neosepta ® CMS cationic membranes, which are selective towards monovalent cations).…”
Section: Cso Membranecontrasting
confidence: 65%
See 1 more Smart Citation
“…Neosepta The high selectivity of the Neosepta ® monovalent-selective cationic exchange membrane results in higher faradic efficiency for lithium(I) and higher permselectivity indexes for lithium(I) with respect to the different divalent cations. The permselectivity index for the Neosepta ® monovalent-selective cationic exchange membrane (P Li/Co = 5.6) is slightly lower than those reported in the work of Afifah et al (2018) [17], i.e., P(Li/Co) = 6.75 at a flowrate of 15 L h −1 and for a voltage of 3 V/Cell with a pack containing 5 pairs of monovalent selective membranes PC-MVA/PC-MVK (initial lithium(I) and cobalt(II) concentration = 100 mg L −1 and 300 mg L −1 , respectively) against P(Li/Co) = 5.6 in this study. However, the value reported in our work regarding the permselectivity index for lithium(I) toward manganese(II) is greater than that obtained by Chan et al [13] (P(Li/Mn) = 5.4 in the present study against P(Li/Mn) = 2.81 at a flowrate of 45 L h −1 and for a voltage of 6 V/Cell with a pack containing 2 pairs of standard anionic membranes PCA PC 400D and 2 Neosepta ® CMS cationic membranes, which are selective towards monovalent cations).…”
Section: Cso Membranecontrasting
confidence: 65%
“…This technology may advantageously reduce the environmental impact, the capital expenditure and operation expenditure of hydrometallurgical processes. However, few studies concern its use in hydrometallurgical processes, and even less address the use of ED in lithium-ion battery recycling processes [13,[16][17][18] Lizuka et al [16] showed that the use of Selemion CMV cation exchange membrane and BP-1E bipolar membrane in electrodializer allowed in recovering selectively 99% lithium(I) from a leaching solution containing 138.82 mg L −1 lithium(I) and 1.179 g L −1 cobalt(II) produced by digesting LiCoO 2 in 1 mol L −1 nitric acid in the presence of 0.8 (vol) % of H 2 O 2 , providing that cobalt(II) was previously complexed by ethylenediaminetetraacetic acid (EDTA) at pH = 4. Likewise, Afifah et al [17] studied the lithium(I)-cobalt(II) separation in nitric acid by electrodialysis by using five pairs of monovalent selective ions exchange membranes (PC Cell membranes PC-MVK/PC-MVA).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the total charge applied, the energy consumptions for ED were 0.24, 0.34, and 0.56 kW h/g Li in the three tests presented above, respectively. Comparing with values reported in the literature of over 192 kW h/g Li through a different ED method, 51 lower energy consumptions show the primary benefits of the proposed process. To precipitate Li 2 CO 3 , the catholyte was heated at 75 °C for 2 h. As a result, the heating step consumed 17 kW h/g Li, which was over 98% of the total energy provided.…”
Section: ■ Experimental Sectionsupporting
confidence: 60%
“…Lithium and cobalt separations with monovalent selective ion exchange membranes such as PC-MVK were demonstrated. The value of the applied potential did not influence significantly the separation efficiency: the rise in voltage from 5 V to 15 V turned the separation factor from 98.6 to 99.4% [ 87 ]. The cobalt ion concentration in the feed solution affected the selectivity of the monovalent ion exchange membrane.…”
Section: Electro-membrane Processes For Lithium Recoverymentioning
confidence: 99%
“…The addition of ion-exchange species on porous electrodes enables selective ion capturing and prevents re-adsorption during the discharge of the electrode [ 80 ]. The nature of the functional groups located on the CDI scaffold affects the electrostatic interactions with ions [ 85 , 86 ], reduces energy requirements [ 87 ], and improves the process stability [ 85 ].…”
Section: Electro-membrane Processes For Lithium Recoverymentioning
confidence: 99%